An Expedient Total Synthesis of Chivosazole F: an Actin‐Binding Antimitotic Macrolide from the Myxobacterium Sorangium Cellulosum. (29th November 2016) - Williams, Simon; Jin, Jialu; Kan, S. B. Jennifer; Li, Mungyuen; Gibson, Lisa J.; Paterson, Ian
Abstract: A unified strategy for the chemical synthesis of the chivosazoles is described. This strategy is based on two closely related approaches involving the late‐stage installation of the isomerization‐prone (2 Z, 4 E, 6 Z, 8 E )‐tetraenoate motif, and an expedient fragment‐assembly procedure. The result is a highly convergent total synthesis of chivosazole F through the orchestration of three mild Pd/Cu‐mediated Stille cross‐coupling reactions, including the use of a one‐pot, site‐selective, three‐component process, in combination with controlled installation of the requisite alkene geometry.